Farm Entrepreneurs’ Intentions to Develop Pluriactive Business Activities in Finland - Tarja Niemelä (Journal of Entrepreneurship, Management and Innovation)

(untitled)
We contribute to the entrepreneurial intentions literature by applying the theory of planned behaviour and resource-based views to the model of active entrepreneurs’ intention to develop their pluriactive usinesses. Using our 2012 survey data from farm firms in Finland, we address the limited focus on active ntrepreneurs and their intentions to develop on-going income-generating, off-farm related business activities. We found that attitudinal proxy antecedents such as innovation, cooperation and growth for pluriactivity differ for active and non-active entrepreneurs and with respect to the entrepreneurs’ age and production line and innovation behaviour.